Longitudinal associations between birth-to-six cortical growth and childhood neurocognitive function - Megan M. Davis; Mackenzie Woodburn; Tehila Nugiel; Divyangana Rakesh; Maresa Tate; William Asciutto; Weili Lin; Jessica R. Cohen; Margaret A. Sheridan (Proceedings of the National Academy of Sciences, 2025)
The human cortex undergoes immense change in the first years of life, doubling in thickness within the first year and evidencing the greatest change within the first 5 y. While substantial research has identified the early postnatal period as a sensitive period in cortical development, research to date lacks the temporal resolution necessary to identify which aspects of cortical change predict later neural and cognitive function. This study leveraged a rich longitudinal dataset of cortical thickness in 50 children who were scanned up to 11 times between birth and 6 y. We used nonlinear multilevel modeling to explore patterns of cortical change across the brain during this period and distinguish whether different phases of change would predict performance and brain activation during a working memory task children completed at approximately 9 y. Cortical thickness across the brain showed a large increase from birth through 12 mo, a decrease from 12 to 18 mo, and a small increase from 18 mo to 6 y, mirroring patterns of early neural proliferation, pruning, and sustained growth. Performance and neural activation during the working memory task were associated with smaller peak (i.e., 12 mo) thickness and a marginally less steep 12 to 18-mo decline in thickness in the middle frontal gyrus (MFG) of the frontal lobe, in line with evidence demonstrating concurrent links between frontal lobe structure and working memory. These findings validate theories of cortical growth developed in preclinical models using human data and demonstrate that prefrontal cortex development in infancy uniquely predicts neurocognitive function 9 y later.